Etiology and outcome of adult and pediatric acute liver failure in Europe - Lenz, Dominic; Hørby Jørgensen, Marianne; Kelly, Deirdre; Cardinale, Vincenzo; Geerts, Anja; Gonçalves Costa, Isabel; Fichtner, Alexander; Garbade, Sven; Hegen, Bianca; Hilberath, Johannes; de Kleine, Ruben; Kupčinskas, Limas; et al. (Journal of pediatric gastroenterology and nutrition, 2023)
Acute liver failure (ALF) is rare but life-threatening. Common causes include intoxications, infections, and metabolic disorders. Indeterminate etiology is still frequent. No systematic data on incidence, causes, and outcome of ALF across Europe are available. Via an online survey we reached out to European Reference Network Centers on rare liver diseases. Numbers and etiology of ALF cases during 2020 were retrieved and diagnostic and treatment availabilities assessed. In total, 455 cases (306 adult, 149 pediatric) were reported from 36 centers from 20 countries. Intoxication was the most common cause in adult and pediatric care. The number of cases with indeterminate etiology is low. Diagnostic tools and specific treatment options are broadly available within this network. This is the first approach to report on etiology and outcome of ALF in the pediatric and adult population in Europe. High diagnostic yield and standard of care reflects the expert status of involved centers.
Gesehen am 31.08.2023